KEBIJAKAN PERUMAHAN DAN PERMUKIMAN BAGI MASYARAKAT URBAN - Soesilowati, Etty (Dinamika, 2007)
The increasing of urbanization tends to generate various problems everywhere, especially in term of basic need services to people such as housing and other facilities. Housing and settlement policy done by government oftentimes fail to accomplish requirement of the resident because of so many interests. This research aimed to identify, descript, interpret and analyze the method of people resettlement, what actors involved in it, what kind of instrument used, and all factors, which supported and blocked. The result of this research showed that mechanism of urban people resettlement from slum and squatters done gradually through pluralism approach, where every step generated policy and collective action among the actors which involved. The actors are not merely the mayor and its connected institutions, but also intellectuals, professionals, communities, entrepreneurs and consultants. This research also showed that the existence of actors, which institutionalized within a network and community such as NGO and group of resident, would be more effective to influence the government policy. Stimulating instrument such as money, used to relocate people, but in fact, such instrument did not guarantee to continue the program. In term of some research findings, the research has contributed to remedy the model of implementation Ã¢â¬ÅhybridÃ¢â¬Â where the formula of resettlement policy always realized in the form of action, but its action is never perfect, so it emerged new policy, in the long time and influenced by outside conditions of organization. In order to guarantee the continual of hybrid instrument program, regulation is necessary to apply beside financial instrument. The practical contribution that the researcher can provide is the use of group based approach.Keywords: Resettlement, Slum and Squatter